Kadar Protein Dan Asam Total Dadih Susu Kambing Etawa Dengan Variasi Penutup Dan Lama Fermentasi - Lestari, Muji; , Dra. Titik Suryani, M.Sc (2015)
The curd is a traditional fermented milk product of West Sumatra. Curd containing lactic acid bacteria as a coagulant. Lactic acid bacteria as probiotics act as resistant acidic conditions. The curd is made by pouring milk into a bamboo Etawa and incubated at room temperature for 48-72 hours. Etawa milk protein, lactose, fat, minerals and total solid. The purpose of this study to determine levels of protein and total acid and organoleptic test milk curd Etawa with cover variations and long fermentation. This research method with a completely randomized design (CRD) with two factors: factor 1: Variations Cover: banana leaf (V1), guava leaves (V2), guava leaf water (V3) and factor 2: Long Fermentation 48 hours (L1 ) 60 hour (L2), 72 hours (L3). Results showed the highest protein content in guava leaf cover water and fermentation 48 hours, the lowest protein content in banana leaf cover and fermentation 60 hours. The highest total acid on banana leaf cover and fermentation 60 hours, the lowest total acid levels in banana leaf cover and fermentation 48 hours. The most dominant curd products yellowish white color, distinctive aroma of goat milk, chewy texture, taste less acidic, thank panelists dominant power like guava cover treatment and fermentation time of 72 hours.